Singgungan Adat dan Budaya Dalam Menentukan Pilihan Politik pada Masyarakat di Kabupaten Mamasa - Djoni Juli; Sabudin Sabudin; Joni Sius (Institut Agama Kristen Negeri Toraja, 2022)
Mamasa is an area that is within the scope of the Uaisapalean Kondosapata Community which is a combination of the initial existence of Pitu Ulunna Salu (PUS) plus other communities formed around PUS. The population in Mamasa Regency is 83% Christian from various church denominations including Catholic Christianity. The Uaisapalean Kondosapata adheres to Ada' Tuo. This study was conducted to determine whether there is an influence of Mamasa customs and culture on the political choices of the Mamasa community at the district, provincial and national levels. This study uses a qualitative approach by interviewing competent sources and understanding the essence of research in data collection. The results showed that there was a fairly strong correlation between Mamasa Customs and Culture on the political choices of the Mamasa community. Customs and Culture in Mamasa Regency differ from one region to another, influencing and shaping communities with different characters.